2015
DOI: 10.1093/europace/euv032
|View full text |Cite
|
Sign up to set email alerts
|

The development of AF over time in patients with permanent pacemakers: objective assessment with pacemaker diagnostics demonstrates distinct patterns of AF

Abstract: NCT02016950, http://clinicaltrials.gov/show/NCT02016950.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
1
17
1
Order By: Relevance
“… 920 This incidence was similar to a separate survey of members of the Heart Rhythm Society. In this survey, an AEF was reported in 6 of 20 , 425 patients (0.03%). 1168 All six of these patients experienced major cerebrovascular events, and five (83%) died.…”
Section: Section 10: Complicationsmentioning
confidence: 67%
“… 920 This incidence was similar to a separate survey of members of the Heart Rhythm Society. In this survey, an AEF was reported in 6 of 20 , 425 patients (0.03%). 1168 All six of these patients experienced major cerebrovascular events, and five (83%) died.…”
Section: Section 10: Complicationsmentioning
confidence: 67%
“…The 2016 European Society of Cardiology guideline recommends that rhythm control reduces rather than eliminates the recurrence of AF, so AADs might be considered as a temporizing rather than a curative treatment . The ATHENA study demonstrated that dronedarone could prevent cardiovascular hospitalization in nonpermanent AF .…”
Section: Discussionmentioning
confidence: 99%
“…There is also marked clinical variability within paroxysmal AF, with some patients having very few short-lived episodes, whilst others have longer periods of AF and short periods of sinus rhythm. However, the cumulative time spent in AF, termed the 'AF density' 15 , has been difficult to accurately measure, given that most outpatient investigations provide only a 'snapshot' view of the heart's rhythm 15 16,17 , but these methods are not applicable to the global population of AF patients.…”
Section: Current Af Classificationmentioning
confidence: 99%